Perlindungan Hukum Konsumen Pengguna Air Minum Isi Ulang Yang Tidak Memenuhi Standar Kualitas Permenkes RI Nomor 492/MENKES/PER/IV/2010 Tentang Pesyaratan Kualitas Air Minum - M. Bram Kurniawan; Syahputra, Bagus Fariza Pratama; Rajali; Heru Pratama; Arbi Yanto (Consensus : Jurnal Ilmu Hukum, 2022)
Drinking water is very much needed by humans for daily needs, such as washing, bathing, and drinking. In addition, drinking water must be clean and healthy, and other requirements for making drinking water must be met. Unclean refilled drinking water can cause diseases such as cholera, malaria, and diarrhea. Companies that provide consumers with refilled drinking water must be responsible for the losses of their consumers. In this case, normative legal research is used. The results of the study show that laws, government regulations, or product quality standards can provide legal protection to consumers. It is very important to ensure that regulations and standards are implemented properly.